Use of laboratory indentation tests to study the surface crack propagation caused by various indenters - Liu, Jie; Jiang, Gangyuan (Engineering fracture mechanics, 2021)
•The CCS indenter was rebuilt by installing cutting teeth.•The built-up indenters can promote surface crack incisions between indentations.•The modified indenter can significantly increase chip mass and further promote indentation efficiency. To study rock breakage between indentations for various indenters, a constant cross section (CCS) indenter and 4 built-up indenters (named W1, M1, M2 and M3) containing various cutting teeth were prefabricated. Then, 25 indentation tests were performed on sandstone specimens using these indenters. The indentation tests show that internal cracks connected the adjacent plastic zones when the indentation depth was relatively large for these indenters. More importantly, the built-up indenters containing various cutting teeth substantially promoted surface crack incisions and formed thick chips for relatively large indentation depths. The subsequent analysis of the indentation efficiency shows that the built-up indenters can promote indentation efficiency for relatively large indentation depths. However, the durability of Indenters W1 and M1 is unsatisfactory. Thus, the built-up indenters (M2 and M3) may be more suitable for promoting surface crack incisions and further increasing the indentation efficiency.